Enhanced forced convection heat transfer of a heat exchanger tube utilizing serrated-ring turbulators - Pimsarn, M.; Samruaisin, P.; Eiamsa-ard, P.; Koolnapadol, N.; Promthaisong, P.; Eiamsa-ard, S. (My University, 2021)
Experiments were performed to study the thermohydraulic behaviors of heating tubes equipped with serrated-ring bundles as turbulators. Their thermohydraulic characteristics are reported in terms of Nusselt numbers (Nu) and friction factors (f) as well as performance in terms of a thermohydraulic performance index (TPI) at identical pumping power. Influences of serrated-ring diagonal angles (θ = 15°, 30°, 45° and 60°), pitch ratios (PR = 6.0, 8.0 and 12.0) and Re were examined. Various geometries of serrated-ring bundles can affect the laminar sub-layer disruption, creating a reversing flow, reconnecting the separated flow to the surface, and delaying the thermal/velocity boundary layer development. These are the most important mechanisms that lead to enhanced force convection heat transfer in a fluid flow. The heat transfer rate, friction loss and TPI increased with decreasing pitch ratio (PR) and serrated-ring diagonal angle (θ ). Heat transfer rate and friction factor were increased to 2.2 and 8.8 times that of a plain tube, respectively. Over the range investigated, the highest TPI, 1.16, was found using a serrated-ring bundle having θ = 15° and PR = 6.0 at Re = 4000.
Keywords: Heat transfer enhancement; Reverse flow; Serrated-ring bundle; Turbulator; Turbulence